Testing of power electronics systems using hardware in the loop - Noor Zalika Kornain,1989-, author; Naziha Ahmad Azli, supervisor; Fakulti Kejuruteraan Elektrik (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2018